Impact Of Brand Identity, Halal Awareness On Purchasing Decisions With Promotional Interventions - Suci Pertiwi; Nasrul Efendi; Tya Wildana Hapsari Lubis; Pioner Pelawi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to determine the influence of brand identity and halal awareness on purchasing decisions, with promotion as an intervening variable. The population includes people who consume imported instant noodles. Using convenience sampling and the Lameshow formula, 96 respondents were surveyed. The hypothesis tests show that brand identity positively affects purchasing decisions, while halal awareness does not. Additionally, promotion does not impact purchasing decisions, but brand identity positively influences promotion. Indirectly, brand identity and halal awareness do not affect purchasing decisions through promotion. The adjusted R square value for purchasing decisions is 0.755, indicating that 75.500 per cent of the variation in purchasing decisions is explained by the independent variables, with 24.500 per cent influenced by other factors not studied.